Sorption and desorption characteristics of sulfamethazine in three different soils before and after removal of organic matter - LI, Xiaona; SONG, Yang; JIA, Mingyun; WANG, Fang; BIAN, Yongrong; JIANG, Xin (Pedosphere, 2021)
Organic matter (OM) is the most critical factor in controlling the sorption-desorption of SMZ in soil, however, few studies have explored the effects of OM removal on these important behaviors among different soils. Batch experiments were conducted to investigate the sorption and desorption characteristics of SMZ in three different soils: fluvo-aquic soil (FS), paddy soil (PS), and red soil (RS). The SMZ sorption in the evaluated soils was dominated by physisorption. The SMZ sorption capacities of FS and PS, which had a relatively higher OM content than RS, were higher than that of RS. The SMZ sorption in FS was dominated by linear partitioning. In contrast, the SMZ sorption in PS and RS was mainly nonlinear surface adsorption. After OM removal, the SMZ sorption capacity was significantly reduced in FS but increased in PS and RS. Furthermore, OM removal restrained the sorption intensity of SMZ in soils. Relatively higher OM and clay contents inhibited the SMZ desorption in FS and PS. The strong negative desorption hysteresis of SMZ in the three soils indicated that SMZ was able to move into the soil solution, thereby posing a risk to humans. Taken together, the findings of this study showed that OM indeed plays an important role during SMZ sorption-desorption in soil.